A Capital Custom: Victoria and the New Zealand Legal Tradition - McLay, Geoff (Victoria University of Wellington Law Review, 2012)
This is the revised text of Geoff McLay’s inaugural lecture given in the Council Chamber at Victoria University of Wellington on 7 June 2011. In the lecture, Professor McLay examines three defining themes of the New Zealand legal tradition and Victoria’s contribution to it: (1) that New Zealand has been, and will continue to be a small place, but linked to a much wider legal world; (2) that the divide between public law and private law is both profoundly important, and at the same time, an illusion; and (3) that New Zealand academic lawyers have sometimes held an unnecessarily narrow view of what counts as law, and that particular legal academics might cast their attention a little wider. The lecture itself can be viewed at <http://mdsweb.vuw.ac.nz/Mediasite/Catalog/>.